Isaac N. Phillips, The Revised Ordinances of the City of Bloomington 58 (1876) - (:unkn) unknown (My University, 1876)
Division 3, Offenses Against Public Safety, Convenience and Health, §1, Firing Cannon, Guns, Fire-Crackers, etc.: Prohibited firing or discharging any cannon, gun, pistol, revolver, or any firearm of any description, or explode any squib, fire-cracker, torpedo, or other thing containing powder or other explosive material. Violators fined not less than two nor more than twenty dollars.
Keywords: DISCHARGE